Perspectivas e contribuições do mestrado profissional em Ciências Ambientais para a formação em educação ambiental - Silva, Jailton Santos (2018)
In the present research we seek to understand how the professional master's degree in environmental science teaching (PROF-CIAMB) contributes to the teaching performance, from the perspective of environmental education (EA) in basic education, since the professional master in teaching appear in the country in order to reflect the professional practice of the masters, in order to impact the realities in which these students work. Thus, the presence of EA in such courses represents the possibility of re-signification of socio-environmental practices carried out in basic education, which contributes to the construction of a critical and socially committed EA. The research is characterized as a case study, based on a quanti-qualitative approach and was developed through information obtained through: documentary research, eleven questionnaires and thirteen semi-structured interviews. The analysis of the data is carried out from the perspective of Discursive Textual Analysis (ATD) from the following categories: teacher education, environmental education, interdisciplinarity, context and curriculum, which emerged from the theoretical framework. The results show that the training carried out by the mentioned postgraduate program has impacted the teaching performance of its students, contributing in the self-reflection of the pedagogical practice and its instrumentalization, through the development of resources and work methodologies, that are incorporated in the schools of basic education where the teachers-students work. In addition, the work with the context category is a more present reality in the practice of these teachers, who seek to link didactic contents to the realities brought by their students. In turn, the understanding of interdisciplinary practice has become clearer and gradually action under this perspective has been sought in basic education, just as the work with environmental awareness has received more attention in classroom practices.